2024
DOI: 10.1186/s12951-024-02421-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-9-5p derived from iPSC-MSCs ameliorates doxorubicin-induced cardiomyopathy by inhibiting cardiomyocyte senescence

Huifeng Zheng,
Xiaoting Liang,
Baojuan Liu
et al.

Abstract: Doxorubicin (DOX) is a chemotherapeutic agent widely used for tumor treatment. Nonetheless its clinical application is heavily limited by its cardiotoxicity. There is accumulated evidence that transplantation of mesenchymal stem cell-derived exosomes (MSC-EXOs) can protect against Dox-induced cardiomyopathy (DIC). This study aimed to examine the cardioprotective effects of EXOs isolated from human induced pluripotent stem cell-derived MSCs (iPSC-MSCs) against DIC and explore the potential mechanisms. EXOs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Recent studies have highlighted the specific role of miRNAs in modulating the functions and therapeutic potential of MSCs. Zheng et al [78] found that exosomal miR-9-5p from iPSC-derived MSCs mitigates doxorubicin-induced cardiomyopathy by preventing cardiomyocyte senescence, primarily through the inhibition of the VPO1/ERK signaling pathway. Human umbilical cord-derived MSCs alleviated myocardial fibrosis and restored miRNA-133a expression in diabetic cardiomyopathy, which positively influenced fibrosis markers and inflammatory mediators in a diabetic mouse model [79].…”
Section: Extracellular Vesicles and Secretomementioning
confidence: 99%
“…Recent studies have highlighted the specific role of miRNAs in modulating the functions and therapeutic potential of MSCs. Zheng et al [78] found that exosomal miR-9-5p from iPSC-derived MSCs mitigates doxorubicin-induced cardiomyopathy by preventing cardiomyocyte senescence, primarily through the inhibition of the VPO1/ERK signaling pathway. Human umbilical cord-derived MSCs alleviated myocardial fibrosis and restored miRNA-133a expression in diabetic cardiomyopathy, which positively influenced fibrosis markers and inflammatory mediators in a diabetic mouse model [79].…”
Section: Extracellular Vesicles and Secretomementioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs) offer a promising solution. They provide an unlimited, reliable source for generating MSCs (referred to as iMSCs) from well-characterized, homogeneous cell lines (see Figure ). These iMSCs can be cultured indefinitely without experiencing replicative senescence, and they exhibit well-defined functions and phenotypes, alleviating many of the technical and biological limitations associated with traditional MSCs.…”
Section: Therapeutic Strategies Targeting Mscs Senescencementioning
confidence: 99%